2021
DOI: 10.1002/lsm.23510
|View full text |Cite
|
Sign up to set email alerts
|

Improved healing and macrophage polarization in oral ulcers treated with photobiomodulation (PBM)

Abstract: Objectives: The effect of photobiomodulation (PBM) treatment on wound healing and macrophage polarization was investigated in vivo. Animal models of oral ulcers were simulated through chemically induced oral ulcers in rats. Materials and Methods: PBM treatment using an infrared pulsed laser was used to treat oral ulcers in the animal models. Twelve Sprague-Dawley rats were randomly divided into four groups depending on set absorbed energy: Group 1 (control), Group 2 (30 J), Group 3 (60 J), and Group 4 (100 J).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
(115 reference statements)
0
7
0
Order By: Relevance
“…1. t-PBM could balance the alterations in peripheral immune cell populations observed in OCD, such as dysregulation of Th17, Treg, monocytes, and the NLRP3 inflammasome complex (Choi et al, 2012;de Barros Silva et al, 2022;de Brito et al, 2022;Guo et al, 2021;Li, Liang, et al, 2020;Ryu et al, 2022;Wu et al, 2022); and modulate the motor cortex (Chaieb et al, 2015;Konstantinović et al, 2013;Song et al, 2020). Furthermore, motor response inhibition, interference control (van Velzen et al, 2014), and increased functional connectivity involving the pre-SMA (Tomiyama et al, 2021) have been observed in patients with OCD.…”
Section: T-pb M a S A P Otential Tre Atment Fo R O Cdmentioning
confidence: 99%
See 3 more Smart Citations
“…1. t-PBM could balance the alterations in peripheral immune cell populations observed in OCD, such as dysregulation of Th17, Treg, monocytes, and the NLRP3 inflammasome complex (Choi et al, 2012;de Barros Silva et al, 2022;de Brito et al, 2022;Guo et al, 2021;Li, Liang, et al, 2020;Ryu et al, 2022;Wu et al, 2022); and modulate the motor cortex (Chaieb et al, 2015;Konstantinović et al, 2013;Song et al, 2020). Furthermore, motor response inhibition, interference control (van Velzen et al, 2014), and increased functional connectivity involving the pre-SMA (Tomiyama et al, 2021) have been observed in patients with OCD.…”
Section: T-pb M a S A P Otential Tre Atment Fo R O Cdmentioning
confidence: 99%
“…Research has suggested that the above‐mentioned mechanisms of t‐PBM may impact the pathophysiology of neuropsychiatric disorders via (1) modulation of oxidative stress (de Freitas & Hamblin, 2016; Molendijk et al., 2014; Rizzi et al., 2006); (2) downregulation of immune cell alterations and the NLRP3 inflammasome complex (Choi et al., 2012; de Barros Silva et al., 2022; de Brito et al., 2022; Guo et al., 2021; Li, Liang, et al., 2020; Ryu et al., 2022; Wu et al., 2022); (3) reduction of proinflammatory cytokines levels such as TNF‐α, CRP, IL‐1β, and IL‐6 (De Marchi et al., 2021; Esteves et al., 2022; Lima et al., 2014; Lu et al., 2017; Shaikh‐Kader et al., 2021; Zheng et al., 2021); (4) deactivation of neurotoxic microglia (Choi et al., 2012; Ketz et al., 2017; Lu et al., 2017; Tao et al., 2021; Wang et al., 2021), and (5) increase of BDNF gene expression (Heo et al., 2019; Yan et al., 2017).…”
Section: Transcranial Photobiomodulation (T‐pbm)mentioning
confidence: 99%
See 2 more Smart Citations
“…In different stages of wound healing, multiple biomarkers work in the orchestra to facilitate the process and advance the healing to the next stage. For example, anti-inflammatory markers such as Transforming growth factor-beta (TGF-β) aid to reduce inflammation and advancing the wound to the proliferation stage [9]. In the first part of our study, we aimed to explore the molecular effect of flaxseed oil on wound healing.…”
Section: Introductionmentioning
confidence: 99%